XX. Literature Review of Smart City Construction and Urban Economic Growth in China Under the One Belt and One Road Initiative - Zhou, Qiuping; Zhang, Xin (The Impact of Digital Economy on One Belt One Road Initiative, 2025)
As the core carrier to promote economic development, cities have significantly contributed to the development of national foreign trade, and smart cities, as a high-level form of future urban development, have an essential impact on the development of urban export trade. Since China officially implemented the construction of smart cities in 2012, it has always considered the construction of smart cities a vital development strategy. Therefore, the study of the impact of smart city construction on urban export trade is of great significance for the effective implementation of smart city construction in China and the exploration of new growth drivers of foreign exchange.